Pengembangan Multimedia Interaktif Berbasis Android pada Materi dan Energi di Program Studi Pendidikan Matematika Universitas Indraprasta PGRI - Mayanty, Sri; Purwanti, Popi; Okyranida, Indica Yona (UNIVERSITAS INDRAPRASTA PGRI, 2023)
This research aims to develop learning media in the form of Android-based interactive multimedia on work and energy materials. The methodology used is research and development, with the ADDIE development model. The instrument used in this research is a questionnaire aimed at material expert validators and media experts. The results of the validity of the media developed are calculated using a percentage score formula and interpreted according to the Likert scale interpretation. The interactive multimedia developed is based on Android so that students are interested and makes it easier for students to understand the material. After validation of the learning media, the average score for all aspects by material experts was 87%, and by media experts it was 88%. Based on the assessment of material experts and media experts, it can be shown that this learning media, in terms of several indicators used for validation, has very good criteria. Then, after being tested on students, the average score for all aspects was 87%, so it can be said that this interactive multimedia, in terms of the indicators used for testing, has very good criteria and is suitable for use as learning teaching material.